Republic of Palau : 2008 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion for Republic of Palau. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Over the past two years, economic activity in Palau has been slowed. Executive Directors welcomed the authorities' disciplined policies, strong financial sector legislation, and prudent management of foreign grants. They encouraged the authorities to build a strong fiscal consolidation and improve the business environment. Directors applauded the authorities' strong efforts to reduce expenditure. They stressed the need for strengthening tax administration and commended the well regulated financial sector, and encouraged the authorities to improve the coverage, reliability, and timeliness of key economic statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet